Artemis Fowl - Colfer, Eoin (Disney/Hyperion Books, 2018)
When a twelve-year-old evil genius tries to restore his family fortune by capturing a fairy and demanding a ransom in gold, the fairies fight back with magic, technology, and a particularly nasty troll.